2017
DOI: 10.1212/wnl.0000000000004216
|View full text |Cite
|
Sign up to set email alerts
|

Mortality trends for multiple sclerosis patients in Sweden from 1968 to 2012

Abstract: There has been a substantial improvement in mortality overall and for each specified cause of death for patients with MS compared with individuals without MS; however, large differences still remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 30 publications
4
43
0
2
Order By: Relevance
“…In the present study, we did not investigate the effect of these changes on social functioning, however several reports from other Table 5 Frequency of first reported symptoms according to birth decades. 1945-1959 1960-1969 1970-1979 1980-1989 1990-1999 countries demonstrated, in recent years, a reduction of hospitalization and mortality related to the disease (Lad et al, 2010;Burkill et al, 2017). Moreover, our study demonstrated that Italian clinicians correctly introduced any new therapy as they were available for patients' treatment.…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, we did not investigate the effect of these changes on social functioning, however several reports from other Table 5 Frequency of first reported symptoms according to birth decades. 1945-1959 1960-1969 1970-1979 1980-1989 1990-1999 countries demonstrated, in recent years, a reduction of hospitalization and mortality related to the disease (Lad et al, 2010;Burkill et al, 2017). Moreover, our study demonstrated that Italian clinicians correctly introduced any new therapy as they were available for patients' treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Surveillance bias, however, is unlikely to be the only explanation for the increased risk, given that hospital admission indicates a relatively serious condition unlikely to be diagnosed by chance during scheduled visits. Infection-related mortality is also higher among MS patients 85,90 , again providing evidence of a genuinely increased risk of infection rather than the association being solely related to surveillance bias. The potential reasons for increased infection susceptibility in MS patients could relate to the effect of immunosuppressive treatments, which could inhibit an immune response to infectious agents 84 .…”
Section: Prognosis For Ms Patientsmentioning
confidence: 90%
“…It is known that life expectancy for MS patients is generally approximately 10 years shorter than life expectancy for the non-MS population, although there have been improvements for MS patients over recent years 85 Alongside common risk factors relating to lifestyle being a possible mechanism for comorbidity in MS patients, there is also evidence to suggest MS patients are at increased risk of developing other autoimmune disorders including asthma, and inflammatory bowel disease. The risk for other diseases such as bipolar disorder, and melanoma are also believed to be increased in MS patients 88 .…”
Section: Prognosis For Ms Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…COD data are used in widely varying settings, ranging from detailed mortality profiles to macro estimates. Applications include studies in localised areas,29 single countries30 or worldwide2 31; for a single-disease32 33 or disease group9; monitored for days or a long-term period7; for specific age groups33 34 or specific situations (eg, maternal mortality,5 external causes35–37). These settings all impose different requirements on the collected data.…”
Section: Discussionmentioning
confidence: 99%